Behavioural Effects of Chronic Immune Activation on Drosophila Aging and Sensitivity to Acute Stress - Tsou, Jonathan (My University, 2015)
The immune response is a complex series of cell-mediated reactions by which an organism combats infection, responds to injury, external stresses, or disease. In both Drosophila melanogaster and vertebrates, aging is associated with progressive declines in physiological functions as well as susceptibility to stress and disease. Naturally, the immune activity is increased with age, yet the efficacy of this response is reduced with age. Conversely, when the immune activation is artificially-induced by Lipopolysaccharide, aging is accelerated. Like aging, neurodegeneration is also associated with increased immune activity. The Blood-Brain barrier (BBB) is a physical barrier with highly selective permeability that isolates the brain from the rest of the body. This barrier is essential for ion homeostasis, and exclusion or efflux of exogenous chemicals. The exclusion properties of the Dm BBB are facilitated by paracellular septate junctions of subperineural glia (SPG), which prevent diffusion into or out of the brain. Using the GAL/UAS system in Drosophila, we found that activation of a glial-specific immune response in either immunodeficiency (IMD) or Toll pathways led to reductions in lifespan and age-dependent negative geotaxis. These reductions were also correlated with an early sensitivity towards oxidative and thermal stresses. Furthermore, we found that a SPG-specific immune response of the Toll pathway or disruption of the paracellular BBB itself was sufficient to show the same reductions as pan-glial activation. In short, we found that flies with CNS-specific immune activation showed an inability to cope with long-term and acute forms of stress, and that SPG-specific Toll Activation was sufficient to show these effects. This implicates chronic immune response as a negative factor during aging, neurodegenerative disease, and brain homeostasis.
Keywords: Chronic Innate Immunity; Aging; Neurodegeneration; Blood-Brain Barrier; Genetics; Drosophila; Glia; Acute Stress